The maintenance of genetic polymorphism in small island populations: large mammals in the Hebrides. - Pemberton, J; Smith, J; Coulson, T; Marshall, T; Slate, J; Paterson, S; Albon, S; Clutton-Brock, T (1996)
Conventionally, small populations living on islands are expected to lose genetic variation by drift. Fluctuations in population size, combined with polygynous mating systems, are expected to contribute to the process by increasing sampling effects on genetic variation. However, in individually monitored populations of Red deer on Rum and Soay sheep on St. Kilda, which experience fluctuations in population size, two processes have been identified which mitigate loss of genetic variation. First, in a number of examples, population reductions are associated with selection. Selection may be in favour of heterozygotes, or, as we have documented in several cases, it may fluctuate in direction temporally. Second, in Soay sheep, in which mortality over population crashes is male-biased, ostensibly leading to low effective numbers of males, molecular studies show that there are systematic changes in the reproductive success of young males, and in variance in male success, that broaden genetic representation compared with expectation.